Bird distributional patterns support biogeographical histories and are associated with bioclimatic units in the Atlantic Forest, Brazil - Carvalho, Cristiano De Santana; Nascimento, Nayla Fábia Ferreira Do; Araujo, Helder F. P. De (Zootaxa, 2017)
Rivers as barriers to dispersal and past forest refugia are two of the hypotheses proposed to explain the patterns of biodiversity in the Atlantic Forest. It has recently been shown that possible past refugia correspond to bioclimatically different regions, so we tested whether patterns of shared distribution of bird taxa in the Atlantic Forest are 1) limited by the Doce and São Francisco rivers or 2) associated with the bioclimatically different southern and northeastern regions. We catalogued lists of forest birds from 45 locations, 36 in the Atlantic forest and nine in Amazon, and used parsimony analysis of endemicity to identify groups of shared taxa. We also compared differences between these groups by permutational multivariate analysis of variance and identified the species that best supported the resulting groups. The results showed that the distribution of forest birds is divided into two main regions in the Atlantic Forest, the first with more southern localities and the second with northeastern localities. This distributional pattern is not delimited by riverbanks, but it may be associated with bioclimatic units, surrogated by altitude, that maintain current environmental differences between two main regions on Atlantic Forest and may be related to phylogenetic histories of taxa supporting the two groups.